Nekatere prehranske možnosti za preprečitev škodljivega vpliva fuzarijskih toksinov (T-2 in DON) na proizvodne lastnosti in lipidno peroksidacijo pri piščancih - Rezar, Vida (Acta agriculturae Slovenica, 2008)
Mycotoxins, a group of secondary fungal metabolites, are toxic for people and animals. Presence of Fusarium toxins (T-2 toxin and deoxinivalenol (DON)) in feed, especially in higher concentrations, reduces feed consumption and consequently live weight gain, which can cause higher economic losses. Recent studies showed that toxins in feed influence the action of the immune system and cause oxidative stress. The objective of the present studies was to: (i) establish the dose dependant effect of T-2 toxin (from 0.5 to 13.5 mg/kg) on production parameters and oxidative stress in broiler chickens, (ii) test the effect of commercial mycotoxin binder at the highest used concentration of T-2 toxin (13.5 mg/kg), and (iii) test the protective effect of nucleotides at high T-2 toxin and DON intoxication (10 mg/kg). Results showed that concentrations of 10 and 13.5 mg/kg of T-2 toxin reduced the feed consumption and live weight gain. T-2 toxin at 10 and 13.5 mg/kg and DON at 10 mg/kg caused DNA damage in leucocytes measured by comet assay. Results proved that supplementation with mycotoxin binder can partly reduce the absorption of mycotoxins from intestine and thus decrease their negative influence on oxidative stress. The crucial role of nucleotide supplementation in feed is to repair DNA damage in immune cells, which are highly sensitive to mycotoxin action.
Keywords: perutnina; piščanci; prehrana živali; krma; mikotoskini; proizvodne lastnosti